PENGARUH SELF ESTEEM, SELF EFFICACY DAN KETERLIBATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. DWI FAJAR SEMESTA DENPASAR - Sapta Rini Widyawati; Ni Ketut Karwini (Forum Manajemen STIMI Handayani Denpasar, 2018)
This study aims to analyze the influence of self efficacy, self esteem andjob involvement on employee performance at PT. Dwi Fajar Semesta Denpasar. Thestudy was conducted in 2017, with data collection techniques through interviews andquestionnaires. Number of respondents 58 employees. The research method used isdescriptive quantitative. The analysis technique used is multiple linear regression,determination analysis and t test with SPSS Version 23 for Windows application. Theresults showed that self esteem, self efficacy and job involvement have a positive andsignificant impact on employee performance at PT. Dwi Fajar Semesta Denpasar.